2015
DOI: 10.1259/bjr.20150126
|View full text |Cite
|
Sign up to set email alerts
|

What is the minimum amount of simulated breast movement required for visual detection of blurring? An exploratory investigation

Abstract: What is the minimum amount of simulated breast movement required for visual detection of blurring? An exploratory investigation. Br J Radiol 2015; 88: 20150126.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…This was not the case for microcalcifications, where detection performance became statistically worse as the magnitude of blurring was increased. The previous work 13 has suggested that motion blur is visible at 0.7 mm for a soft-edged blur, and our work seems to confirm this. This could have implications for practice as it could mean that when blur is observed in an image, repeat imaging should be considered as in clinical work one would simply not know how much blurring is present and what impact it is having.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This was not the case for microcalcifications, where detection performance became statistically worse as the magnitude of blurring was increased. The previous work 13 has suggested that motion blur is visible at 0.7 mm for a soft-edged blur, and our work seems to confirm this. This could have implications for practice as it could mean that when blur is observed in an image, repeat imaging should be considered as in clinical work one would simply not know how much blurring is present and what impact it is having.…”
Section: Discussionsupporting
confidence: 88%
“…13 Simulated motion blur was applied using a convolution mask that provided a 3 standard deviation (3SD) distribution of blur over the desired blur radius. The 3SD range is consistent with the application of a Gaussian blur mask, typically used to generate generic blur effects (equivalent to a semi-transparent film being placed over an image).…”
Section: Simulated Blurring and Image Displaymentioning
confidence: 99%
See 2 more Smart Citations
“…1 Motion blur can occur for various reasons, including patient movement and paddle motion during the clamping phase. 1,3 Blurry mammograms may need to be repeated; one screening unit in the UK reported that image blur is the main reason for 90% of recalls. 4 Furthermore, one screening service reported that 0.86% of screening candidates were recalled because of blurred mammograms.…”
Section: Introductionmentioning
confidence: 99%